Asymmetric Catalysis: Science and Opportunities (Nobel Lecture) - Noyori, Ryoji (Angewandte Chemie International Edition, 2002)
Asymmetric catalysis, in its infancy in the 1960s, has dramatically changed the procedures of chemical synthesis, and resulted in an impressive progression to a level that technically approximates or sometimes even exceeds that of natural biological processes. The recent exceptional advances in this area attest to a range of conceptual breakthroughs in chemical sciences in general, and to the practical benefits of organic synthesis, not only in laboratories but also in industry. The growth of this core technology has given rise to enormous economic potential in the manufacture of pharmaceuticals, animal health products, agrochemicals, fungicides, pheromones, flavors, and fragrances. Practical asymmetric catalysis is of growing importance to a sustainable modern society, in which environmental protection is of increasing concern. This subject is an essential component of molecular science and technology in the 21st century. Most importantly, recent progress has spurred various interdisciplinary research efforts directed toward the creation of molecularly engineered novel functions. The origin and progress of my research in this field are discussed. From sub‐femtomole to ton scale: Asymmetric catalysis with organometallic complexes plays a major role in all areas of modern synthetic chemistry. The author has worked in this area since the beginning and has been honored for his research with the Nobel prize. Asymmetric hydrogenation with transition‐metal complexes of BINAP ligands (see picture) has been an important step in his personal research career.